Optimizing Antenatal Care: The Effects of a Holistic Nursing Android Application for Pregnant Women - Desmawati, Desmawati; Ismail, Rita (Department of Nursing, Faculty of Medicine, Universitas Diponegoro, 2024)
Background: During the COVID-19 pandemic, face-to-face antenatal care (ANC) services were limited. Therefore, we developed the Android digital application “Guide Me” with a holistic care concept for optimizing ANC.Purpose: This study aimed to evaluate the effect of the Android digital application “Guide Me” on optimizing ANC. Methods: The present study used an experimental research design. The participants included 302 pregnant women selected through block randomization, with 160 in the intervention group and 142 in the control group. The intervention involved providing ANC services using a digital Android application at home, with health services visited only when treatment was necessary. The intervention group received usual care along with the Android application, “Guide Me”, which included a holistic nursing concept program, while the control group received only the usual care. Data were collected three times, and the ANC scale was used to measure ANC optimization. Repeated measures ANOVA was used to analyze the data.Results: There were significant differences in the optimization of ANC ([F=96.887, df (1,300), p<0.001]) between the intervention and control groups. The target of 14 T in the intervention group showed significant statistical differences over three times ([F=118.35, df (1,308), p<0.001]) compared to the control group, with optimization of ANC increasing from 45.79 to 59.16 in the intervention group and from 44.09 to 45.77 in the control group.Conclusions: The program effectively increased ANC optimization. Pregnant women feel more at ease in their own homes and have less time to visit a hospital. Therefore, they may accept and even appreciate online apps and telemonitoring as alternatives to ANC checks.